BUSINESS MODEL CANVAS (BMC) ANALYSIS IN THE MANAGEMENT OF THE PROSPEROUS SHEEP FARMING PROGRAM (TDS) TO ENHANCE MUSTAHIK INCOME AT THE NURUL HAYAT AMIL ZAKAT INSTITUTION (LAZ) JEMBER - Zainullah Zainullah; Moch. Chotib; Ahmad Afif (Adisam Publisher, 2025)
Zakat-based economic empowerment programs serve as a vital instrument in enhancing the welfare of mustahik (zakat recipients) in Indonesia, particularly amid the persistent challenges of poverty. The Nurul Hayat Zakat Management Institution (LAZ) in Jember implements the Ternak Domba Sejahtera (TDS) or Prosperous Sheep Farming Program as an initiative to utilize productive zakat in supporting the income of mustahik. This study focuses on analyzing the business model of the TDS program in order to optimize the management of productive zakat and drive the economic transformation of mustahik. The research is centered on three main aspects: the management of the TDS program by LAZ Nurul Hayat Jember, changes in mustahik income after participating in the program, and an analysis of the implementation of the Business Model Canvas (BMC) in the program. The objective of this research is to describe the management process of the TDS program, analyze its impact on mustahik income, and evaluate the application of the BMC within the program. This study aims to provide strategic recommendations for optimizing the productive zakat business model within zakat management institutions. The research employs a qualitative descriptive method with a case study approach. Data were collected through in-depth interviews, field observations, and documentation at LAZ Nurul Hayat Jember as well as with mustahik beneficiaries in Curah Manis Hamlet, Sidomulyo Village, Silo Sub-district, Jember. Data validity was maintained through triangulation of sources and techniques. The research findings reveal that the management of the TDS program involves intensive mentoring, the distribution of capital in the form of sheep, and regular monitoring by the LAZ team. The income of mustahik increased significantly after participating in the program, supported by a profit-sharing system and entrepreneurship training. The implementation of the BMC effectively maps out the nine key business elements, such as customer segments, value propositions, channels, and key activities. Synergy with local partners and efficient cost management strengthen the sustainability of the program. However, challenges remain in the areas of marketing and the capacity building of mustahik. The analysis of the Business Model Canvas in the management of the TDS program has proven effective in increasing mustahik income and reinforcing the productive zakat empowerment model at LAZ Nurul Hayat Jember, although innovation is still needed in marketing strategies and in enhancing the entrepreneurial capacity of mustahik.